Clinical Effectiveness of Bilateral Extended ESP Block in Cardiac Surgery Patients with Median Sternotomy under Conditions of Artificial Blood Circulation - Ruslan M. Taran; Vyacheslav V. Osaulenko; Karina O. Chmul; Serhii I. Vorotyntsev (Ukrainian Journal of Cardiovascular Surgery, 2025)
Relevance. Opioid analgesics are always used to provide adequate analgesia, but may carry risks of complications and formation of chronic pain syndrome.Aim. To evaluate the clinical effectiveness of bilateral extended blockade of the plane of the extensor back muscles (ESPB) as a component of multimodal analgesia in cardiosurgical operations with median sternotomy under conditions of artificial blood circulation.Materials and methods. A single-center retrospective-prospective observational study included 123 patients who underwent cardiac surgery on the heart with a median sternotomy with artificial blood circulation. The average age of the patients was 60 ± 1.5 years; there were 80 (65%) men and 43 (35%) women. Patients were divided into two groups: group 1 (n=57, 46%) – control, where narcotic analgesics were used for perioperative analgesia; group 2 – research group (n=66, 54%), ESP-block and fentanyl (if necessary).End points of the study: primary – total dose of narcotic analgesics in the first 48 hours after extubation; secondary – intraoperative consumption of fentanyl, stability of hemodynamic indicators during surgery, dynamics of indicators of acid-base status, glycaemia and blood lactate level, time to extubation of the trachea, intensity of postoperative pain according to the visual-numerical assessment scale (NRPS), the need to prescribe narcotic analgesics, activation and mobility of patients, length of stay in the intensive care unit.The Statistica package (Stat Soft Statistica v.13.0) and Microsoft Excel 2013 (license 00331-10000-00001-AA4040) were used for statistical data processing.Results. Total intraoperative fentanyl requirement was lower in group 2 than in group 1 (3 ± 0.05 μg/kg vs. 15 ± 0.05 μg/kg, respectively, p < 0.01). Hemodynamic indicators in both groups at the stages of surgical intervention were within the limits of reference values. However, in group 2, blood pressure and heart rate remained more controlled and stable during the operation (p < 0.01). The lactate level increased in both groups at the end of the operation, but in group 2 it was 1.6 times lower than in group 1 and was within the reference values (2.3 ± 1.3 mmol/L vs. 3.63 ± 1.83 mmol/L, respectively, p < 0.01).The pain intensity according to the numerical pain rating scale (NRPS) in group 2 was on average 3 times less than in group 1 during 48 hours after surgery (p < 0.01). Narcotic analgesics were prescribed to only 4 (6.06%) patients in group 2, while in group 1, the need to prescribe narcotics was in 49 (80.6%) patients (p < 0.01).Conclusions. The use of a bilateral extended ESP block in patients with a cardiosurgical profile with median sternotomy under conditions of artificial blood circulation leads to a decrease in the perioperative consumption of fentanyl and the intensity of postoperative pain, which contributes to early extubation of the trachea and shortens the time the patients stay in the intensive care unit.